School’s Performance and Head Teachers’ Leadership Styles: A Comparative Study of Low-Performing and High Performing Schools - Pokhrel , Tika Ram; Singh, Jal Krishna (JMC Research Journal, 2025)
Though the responsibility of the Head Teacher (HT) is not only to promote the results of learning assessments, s/he is more responsible for the overall performance of a school. How the leadership style of HT and the school performance in terms of Secondary Education Examination (SEE) results are related to each other is the main problem in Nepalese community schools. Explorative research, a qualitative research method, was used to explore the leadership styles of HTs. The School Management Committee (SMC) Chair, an HT, and a teacher from each high and low-performing school were selected as research participants. Interview and observation were the two main methods of data collection. Leadership practices are based on their leadership styles like decision making, communication, motivation, responsibility and integrity, power and authority, and school culture, based on the existing practices of high and low-performing schools. HT was perceived as a more democratic leader in high-performing schools. In the case of low-performing schools, the practice of leadership followed by HT is more autocratic concerning decision-making and teachers' autonomy. Teachers and SMC chairs viewed the leadership practice of low-performing schools as ambiguous. Having good perceptions and practices creates a favorable learning environment, which helps improve students’ overall performance. School leadership style is expected to be favorable to improve school performance. A favorable school culture is helpful in enhancing the quality of education.